(untitled) (Experimental biology, 2017)
In laboratory studies were identified and selected key parameters and conditions of cultivation of multi-component compositions and formulated rules for mnogokomponennyh compositing microorganisms to clean soil and oil sludge and oilcontaminated soil and sludge decontamination technology.